2022
DOI: 10.1136/jitc-2022-004952
|View full text |Cite|
|
Sign up to set email alerts
|

Short-term dynamics of circulating tumor DNA predicting efficacy of sintilimab plus docetaxel in second-line treatment of advanced NSCLC: biomarker analysis from a single-arm, phase 2 trial

Abstract: ObjectiveRobust biomarker predicting efficacy of immunotherapy is limited. Circulating tumor DNA (ctDNA) sought to effectively monitor therapeutic response as well as disease progression. This study aims to investigate predictive role of ctDNA short-term dynamic change (6 weeks postimmunotherapy) in a single-arm, phase 2 trial of sintilimab plus docetaxel for previously treated advanced non-small cell lung cancer (NSCLC) patients.MethodsA total of 33 patients with advanced NSCLC with disease progression during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 52 publications
(53 reference statements)
0
6
0
Order By: Relevance
“…Song et al monitored ctDNA dynamics in a longitudinal cohort of advanced NSCLC patients and found that the ctDNA clearance at any timepoint during treatment was associated with a longer PFS 38 . Han et al evaluated the predictive value of ctDNA clearance (C2) in second-line chemotherapy (6 weeks post-treatment), and found it to be an independent risk factor for PD or death 39 . The Camel-Sq trial revealed that the mean variant allele frequencies of variants at C2 had a strong association with ORR.…”
Section: Discussionmentioning
confidence: 99%
“…Song et al monitored ctDNA dynamics in a longitudinal cohort of advanced NSCLC patients and found that the ctDNA clearance at any timepoint during treatment was associated with a longer PFS 38 . Han et al evaluated the predictive value of ctDNA clearance (C2) in second-line chemotherapy (6 weeks post-treatment), and found it to be an independent risk factor for PD or death 39 . The Camel-Sq trial revealed that the mean variant allele frequencies of variants at C2 had a strong association with ORR.…”
Section: Discussionmentioning
confidence: 99%
“…The Clopper-Pearson method for the estimation of objective response rates and disease control, and the use of two-sided tests at the 0.05 significance level, as in the study of docetaxel plus sintilimab, highlight the rigor in comparing treatments' efficacy [63]. Furthermore, advanced techniques like cross-validation for the determination of the optimal cut-off for the bTMB and the minimum p-value approach reflect the ongoing evolution of statistical methods in oncological research [54].…”
Section: Findings Of the Studiesmentioning
confidence: 99%
“…Currently, numerous studies have provided evidence that ctDNA-based biomarkers are essential for guiding immunotherapy and predicting its subsequent efficacy ( Wang et al, 2022c ; Peters et al, 2022 ; Sun et al, 2022 ). One such study by Han et al employed ctDNA to forecast the effectiveness of sintilimab plus docetaxel in the second-line treatment of advanced NSCLC ( Han et al, 2022 ). Blood samples were prospectively collected at baseline and after 2 cycles of treatment (6 weeks after treatment) to describe the landscape of high-frequency genomic profiles at baseline and week 6 ( Han et al, 2022 ).…”
Section: Ctdna and The Adjuvant Therapy Of Nsclcmentioning
confidence: 99%
“…One such study by Han et al employed ctDNA to forecast the effectiveness of sintilimab plus docetaxel in the second-line treatment of advanced NSCLC ( Han et al, 2022 ). Blood samples were prospectively collected at baseline and after 2 cycles of treatment (6 weeks after treatment) to describe the landscape of high-frequency genomic profiles at baseline and week 6 ( Han et al, 2022 ). Major molecular features of preselected genes associated with response to second-line chemoimmunotherapy were analyzed.…”
Section: Ctdna and The Adjuvant Therapy Of Nsclcmentioning
confidence: 99%
See 1 more Smart Citation